The TRANSFORMATION BASED ON OUTCOMES PERFORMANCE ASSESSMENT INSTRUMENTATION MODEL 0F THE NATIONAL STANDARD OF EDUCATION TO THE BALANCED SCORECARD : Case Studies in Senior High Schools in North Sumatra Province, Indonesia - -, Saut; Siburian, Paningkat; Pangaribuan, Wanapri (Advances in Social Sciences Research Journal, 2020)
Abstract The performance assessment of the outcomes of a high school must use a valid and reliable assessment instrument. The instrument model for an outcomes performance assessment that is built from the transformation of the National Education Standards to the Four Balanced Scorecards perspectives produce 65 assessment items that are valid and have high reliability. High school outcomes performance assessment in North Sumatra can be done by using a formulated model of an outcomes performance assessment instrument so that the hope is that the quality of SMA can be improved.